The effect of religious coping and prosocial behaviors on secondary traumatic stress in nurses - Yakup Sarpdağı; Muhammet Faruk Yiğit; Ebubekir Kaplan; Özkan Sir; Necmettin Çiftci; Hakan Orakçi; Metin Yildiz (BMC Nursing)
Abstract Background Nurses are routinely exposed to traumatic events as part of their professional duties, placing them at risk of developing secondary traumatic stress (STS). This condition can negatively impact both their psychological well-being and job performance. Although religious coping strategies and prosocial behaviors are thought to play a protective role against STS, these effects remain understudied in the literature. Methods This descriptive and cross-sectional study was conducted with the participation of 516 nurses. Data were collected between April and August 2024 using the ‘Sociodemographic Data Form’, Religious Coping Scale’, “Prosocial Behavior Scale” and “Secondary Traumatic Stress Scale”. In the study, hierarchical regression analysis was applied to examine the effect of independent variables on the dependent variable. Results 58.6% of the nurses were between the ages of 18–31, 58.4% were undergraduate graduates, and 82.6% had experienced a traumatic event. The mean score of prosocial behavior was 3.04 ± 0.63 and the mean score of secondary traumatic stress was 48.98 ± 13.52. Positive religious coping (mean = 20.02 ± 4.31) showed a moderate negative correlation with secondary traumatic stress (r=-0.563, p = 0.001). Hierarchical regression revealed that religious coping strategies (positive and negative religious coping) alone explained 31.8% of the variance in secondary traumatic stress (R²=0.318), and when prosocial behavior was added, this percentage increased to 33.9%. Conclusions This study highlights the critical role of positive religious coping and prosocial behavior in reducing secondary traumatic stress among nurses frequently exposed to traumatic events. Positive religious coping emerged as the strongest protective factor, while prosocial behavior also contributed significantly to the reduction of stress levels. Strengthening positive coping mechanisms and promoting prosocial behaviors may be effective strategies to support nurses’ mental health and resilience in trauma intensive care settings. Clinical implications Positive religious coping and prosocial behaviors were found to be effective in reducing nurses’ secondary traumatic stress. It is recommended that training and support programmes that support nurses’ positive coping skills should be expanded in clinical practice.